Análise das propriedades geotécnicas de misturas de solo e biochar de casca de coco para aplicação em camadas de cobertura de aterro sanitário - Tavares, Vitória Lima (2024)
The final cover layer of a landfill is crucial for environmental protection, serving to minimize water infiltration into deposited solid waste and mitigate greenhouse gas emissions to the atmosphere. Incorporating biochar into the soil emerges as an effective alternative to enhance cover soil properties, improving physical, chemical, and biological characteristics and intensifies the water retention capacity. This study aims to evaluate the suitability of biocharamended soil for landfill cover systems based on their geotechnical properties. Laboratory experiments were conducted, involving the production of coconut husk biochar (CHB) and the geotechnical characterization of soil and biochar-amended soil with varying biochar contents (2.5%, 5.0%, 7.5%, and 10.0%, w/w). Hydraulic conductivity, direct shear, and consolidation tests were performed, and water retention curves (WRC) were measured using the filter paper method to assess unsaturated hydraulic properties. The results identify the biochar-amended soil that best aligns with current standards for the cover layer system. The most viable option for application in the cover layer of landfills was the 5% biochar-amended soil, as it best complies with national and international regulatory parameters. Additionally, the addition of biochar to the soil induced changes such as water retention capacity, reduced compressibility, and minimal alterations in hydraulic conductivity. This study contributes for a better analysis of the requirements and properties to be considered in column tests in the laboratory and even to analyze criteria for design, execution, and maintenance of methane oxidative layer for use in landfills with similar climate and soil characteristics.